2020
DOI: 10.1002/npr2.12119
|View full text |Cite
|
Sign up to set email alerts
|

Vexin is upregulated in cerebral cortical neurons by brain‐derived neurotrophic factor

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…At DIV6, BDNF was applied with a final concentration of 10 ng/mL 22 . Cells were lysed in RLT butter (RNeasy mini kit, Qiagen) for NGS library preparation at DIV 8, after 48 hours of BDNF incubation 23–25 . Striatal cells at DIV6 were fixed with 4% paraformaldehyde for immunostaining.…”
Section: Methodsmentioning
confidence: 99%
“…At DIV6, BDNF was applied with a final concentration of 10 ng/mL 22 . Cells were lysed in RLT butter (RNeasy mini kit, Qiagen) for NGS library preparation at DIV 8, after 48 hours of BDNF incubation 23–25 . Striatal cells at DIV6 were fixed with 4% paraformaldehyde for immunostaining.…”
Section: Methodsmentioning
confidence: 99%
“…S3b). Previously undescribed enriched mRNAs included Nell2 89,90 , which is involved in neuronal polarization and axon growth, Ankrd46, associated with membrane interactions, and the uncharacterized Vnx 91,92 (Fig. 3d, Extended Data Fig.…”
Section: Enriched Mrnas and Proteins In S Oriensmentioning
confidence: 99%
“…Our study found that it may be one of the characteristic biomarkers of PA, and further research is needed to explore its role in tumor development and its relationship with TME.Chromosome 8 open reading frame 46 (C8orf46), a human protein-coding gene, has been named Vexin. Previous studies have suggested that Vexin is involved in embryonic neurogenesis and is related to cancer progression, but its function has not yet been elucidated clearly(Koshimizu et al 2020, Moore et al 2018). Our study is the rst to report that this gene is associated with PA, which provides a new direction for future research.…”
mentioning
confidence: 99%